A broad inhibitor of acyl-acyl carrier protein synthetases - Todorinova, Magdalena; Beld, Joris; Jaremko, Kara L. (Biochemistry and biophysics reports, 2023)
The acyl-acyl carrier protein synthetase enzyme enables some bacteria to scavenge free fatty acids from the environment for direct use in lipids. This fatty acid recycling pathway can help pathogens circumvent fatty acid synthase (FAS) inhibition with established antibiotics and those in clinical development. AasS enzymes are surprisingly hard to identify as they show high sequence similarity to other adenylate forming enzymes, and only a handful have been correctly annotated to date. Four recently discovered AasS enzymes from Gram negative bacteria, Chlamydia trachomatis, Neisseria gonorrhoeae, and Alistipes finegoldii, form distinct clusters in protein sequence similarity networks and have varying substrate preferences. We previously synthesized C10-AMS, an inhibitor of AasS that mimics the acyl-AMP reaction intermediate. Here we tested its ability to be broadly applicable to enzymes in this class, and found it inhibits all four newly annotated AasS enzymes. C10-AMS therefore provides a tool to study the role of AasS in fatty acid recycling in pathogenic bacteria as well as offers a platform for antibiotic development. [Display omitted] •Four recently annotated acyl-acyl carrier protein synthetases were tested in vitro.•These AasSs group in distinct clusters suggesting significant differences.•All AasSs were active with EcACP and C10 substrates.•C10-AMS inhibited all four AasS enzymes.